Exploring the Scientific Utility of Combined Spaceborne Lidar and Lightning Observations of Thunderstorms - Timothy J. Lang; Sarah D. Bang (Earth and Space Science, 2022)
Abstract Approximately 8 months of colocated spaceborne lidar and lightning observations were analyzed in a pathfinder study to understand the advantages and challenges of using these combined observations to understand thunderstorms. Data from the Lightning Imaging Sensor (LIS) and the Cloud‐Aerosol Transport System (CATS) lidar were used when they overlapped on the International Space Station during March–October 2017. Using simple matching criteria, 8246 LIS flashes occurred within 25 km of the CATS ground track. CATS cloud top heights near these flashes showed similar behavior with latitude when compared with a spaceborne radar‐based climatology, but the lidar cloud tops were approximately 2‐km higher than 20‐dBZ radar echo tops. CATS cloud phase near LIS flashes was consistent with ice‐ or mixed‐phase more than 90% of the time, showing the value of using lightning observations to validate lidar‐based feature masks. In addition, correlations between a proxy for LIS flash rate and CATS ice water path, cloud optical depth, and cloud top height were low (0.38–0.42) but positive and highly statistically significant (>99%), suggesting that lidar retrievals of cloud properties can be meaningfully compared with lightning observations despite lidar's known inability to penetrate deeply into optically thick clouds like thunderstorms. Finally, CATS was used to help diagnose LIS false alarms due to surface‐based glint. The false alarm rate was approximately 0.1%, which demonstrated the excellent performance of the surface glint filter in the LIS processing code. The results suggest that fruitful scientific insights can be expected from larger combined lidar/lightning datasets.